Design and Evaluation of a Web-Based Helpdesk Ticketing System Using Extreme Programming for Improving IT Service Efficiency - Stefanus Satryo Wasono; Ananda Syarif Hidayatullah; Rian Mohamad Said; Syifaurachman Syifaurachman (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2026)
Helpdesk solutions are essential for the proper management of IT service requests within enterprises. Nonetheless, numerous companies continue to depend on manual communication methods, such as telephone and email, resulting in protracted response times, disorganized data, and ineffective service management. This study is to create and assess a web-based helpdesk ticketing system utilizing the Extreme Programming (XP) methodology to enhance IT service efficiency. This research is executed as a case study at PT. INFOSIS-BLU, an IT service firm where the current helpdesk procedure yields an average response time of 6–8 hours and is devoid of centralized documentation. The suggested system incorporates real-time ticket monitoring, technician allocation, and centralized data management to optimize service operations. The assessment results indicate substantial enhancements, comprising a 30% augmentation in operating efficiency, a decrease in response time to below 10 minutes, and user satisfaction attaining 85%. The data demonstrate that XP is proficient in creating flexible and efficient helpdesk systems.